CLINICAL PROFILE AND COMPARISON OF OUTCOME OF TREATMENT BY EXTRACORPOREAL SHOCK WAVE LITHOTRIPSY AND URETERORENOSCOPY IN THE MANAGEMENT OF UPPER URETERIC CALCULI - SINGH BASRA, SHARANJIT; RN, HIREMATH; VERMA, VISHAL; KUMAR, DOBI SRAVAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Urinary calculi are the third most common affliction of the urinary tract, exceeded only by urinary tract infections and pathologic conditions of the prostate. This study was carried out to assess the safety, efficacy, and compare structural and functional outcome after treating the patients of the upper ureteric calculus with Extracorporeal Shock Wave Lithotripsy (ESWL) and Ureterorenoscopy (URS). Methods: A prospective study was conducted on patients with the upper ureteric stone of size 0.5–1.5 cm. A total of 50 patients were included in the study by means of systematic random sampling so as to get 25 patients in each category of ESWL and URS for the treatment of their upper ureteric calculi. Results: The age ranged from 15 years to 55 years. There were 36 males and 14 females in the study of 50 patients, 43 (86%) presented with pain, followed by 4 (8%) presented with hematuria. Twenty-eight (56%) of the patients had stone in the range of 0.5–1.0 cm, and 22 (44%) of the patients had stone in the range of 1.0–1.5 cm. Sixteen (32%) patients had stone within 2 cm of the pelvi-ureteric junction, and 13 (26%) had stone within 2 cm of the sacroiliac joint. Twenty-one (42%) patients had stone in between these two. Of the 50, 25 patients (50%) underwent shock wave lithotripsy, 25 patients (50%) underwent URS. In the ESWL group, 21 (84%) patients were stone-free after single sitting of ESWL. Four patients (16%) who required Re ESWL, after repeat ESWL two became stone-free however 2 (8%) patient of 1.0–1.5 cm category required secondary procedure, that is, URS and became stone free. To achieve stone-free 1.24 procedure was required per patients. Of the 25 patients in the ESWL group, 2 (8%) patient (one steinstrass case and one poor fragmentation case) required secondary procedure. They underwent URS. Both the patient belonged to 1.0–1.5 cm group. URS was done using semirigid ureteroscope using pneumatic Lithoclast. In our study, two patients of each 0.5–1.0 cm and 1.0–1.5 cm category did not become stone free. These four patients were subjected to ESWL and became stone free. Conclusion: The management of the ureteral stone should be decided on individual basis, based on stone size, location, symptoms, obstruction, and the availability of the instruments. For stones of 0.5–1.0 cm, ESWL is the treatment of choice for the upper ureteric stones, with very low Re- ESWL (1.12 sittings) without any requirement of ancilliary procedure. URS may be used for the upper ureteric stones but requirement of ancilliary procedure is high 11.11%. For stones between 1.1 cm and 1.5 cm, ESWL is the preferred modality of treatment for the upper ureteric stones.